Treatment Characteristics and Real-World Progression-Free Survival in Patients With Unresectable Stage III NSCLC Who Received Durvalumab After Chemoradiotherapy: Findings From the PACIFIC-R Study - Girard, Nicolas; Bar, Jair; Garrido, Pilar; Garassino, Marina C.; McDonald, Fiona; Mornex, Françoise; Filippi, Andrea R.; Smit, Hans J.M.; Peters, Solange; Field, John K.; Christoph, Daniel C.; Sibille, Anne; et al. (Journal of Thoracic Oncology, 2022)
Introduction: The phase 3 PACIFIC trial established consolidation therapy with durvalumab as standard of care for patients with unresectable, stage III NSCLC and no disease progression after definitive chemoradiotherapy (CRT). The observational PACIFIC-R study assesses the real-world effectiveness of durvalumab in patients from an early access program. Here, we report treatment characteristics and a preplanned analysis of real-world progression-free survival (rwPFS). Methods: PACIFIC-R (NCT03798535) is an ongoing, international, retrospective study of patients who started durvalumab (intravenously; 10 mg/kg every 2 wk) within an early access program between September 2017 and December 2018. The primary end points are investigator-assessed rwPFS and overall survival (analyzed by Kaplan–Meier method). Results: As of November 30, 2020, the full analysis set comprised 1399 patients from 11 countries (median follow-up duration, 23.5 mo). Patients received durvalumab for a median of 11.0 months. Median rwPFS was 21.7 months (95% confidence interval: 19.1–24.5). RwPFS was numerically longer among patients who received concurrent versus sequential CRT (median, 23.7 versus 19.3 mo) and among patients with programmed cell death-ligand 1 expression greater than or equal to 1% versus less than 1% (22.4 versus 15.6 mo). Overall, 16.5% of the patients had adverse events leading to treatment discontinuation; 9.5% of all patients discontinued because of pneumonitis or interstitial lung disease. Conclusions: Consolidation durvalumab after definitive CRT was well tolerated and effective in this large, real-world cohort study of patients with unresectable, stage III NSCLC. As expected, rwPFS was longer among patients who received concurrent versus sequential CRT and patients with higher programmed cell death-ligand 1 expression. Nevertheless, favorable rwPFS outcomes were observed regardless of these factors.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Consolidation therapy; Immunotherapy; Locally advanced NSCLC; PD-L1 inhibition; Real-world data